Impact of tumour necrosis factor inhibitor treatment on radiographic progression in rheumatoid arthritis patients in clinical practice: results from the nationwide Danish DANBIO registry. Issue 1 (24th April 2012) - Ørnbjerg, Lykke Midtbøll; Østergaard, Mikkel; Bøyesen, Pernille; Krogh, Niels Steen; Thormann, Anja; Tarp, Ulrik; Poulsen, Uta Engling; Espesen, Jakob; Ringsdal, Vibeke Stevenius; Graudal, Niels; Kollerup, Gina; Jensen, Dorte Vendelbo; et al.
Abstract : Objectives: To compare radiographic progression during treatment with disease-modifying antirheumatic drugs (DMARD) and subsequent treatment with tumour necrosis factor α inhibitors (TNF-I) in rheumatoid arthritis (RA) patients in clinical practice. Methods: Conventional radiographs (x-rays) of hands and wrists were obtained ∼2 years before start (prebaseline), at baseline and ∼2 years after start (follow-up) of TNF-I. Clinical data were obtained from the DANBIO registry and the patient files. x-Rays were scored blinded to chronology according to the Sharp/van der Heijde method. Annual radiographic progression rates during the DMARD (prebaseline to baseline x-ray) and TNF-I (baseline to follow-up x-ray) periods were calculated. Results: 517 RA patients (76% women, 80% IgM rheumatoid factor positive, 65% anticyclic citrullinated peptide positive, 40% current smokers, age 54 years (range 21–86), median disease duration 5 years (range 0–57)) were included. Patients were treated with infliximab (61%), etanercept (15%) or adalimumab (24%). During the DMARD period 85% of patients received methotrexate, 51% sulphasalazine and 78% prednisolone. The median DMARD period was 733 days (IQR 484–1002) and the median TNF-I period was 562 days (IQR 405–766). The median radiographic progression rate decreased from 0.7 (IQR 0–2.9) total Sharp score units/year (dTSS) in the DMARD period to 0 (0–0.9) units/year in the TNF-I period (p<0.0001, Wilcoxon). Corresponding mean dTSS values were 2.1 (SD 3.7) versus 0.7 (SD 2.3) units/year (p<0.0001, paired t test). 305 patients progressed (dTSS >0) in the DMARD period compared with 158 patients in the TNF-I period (p<0.0001, χ 2 ). Conclusion: This nationwide observational study of RA patients documented significantly reduced radiographic progression during TNF-I treatment compared with the previous period of DMARD treatment.